Protective effects of Shenkang injection against diabetic kidney disease via p38 MAPK/NFκB/MCP-1/CCR2 pathway inhibition - Zhou, Xin; Wang, Sitong; Jin, Ge; Zhou, Kaidong; Cai, Yanmo; Zhao, Zongjiang (Frontiers in Endocrinology, 2025)
BackgroundDiabetic kidney disease (DKD) is a complication of microvascular disease that occurs in the late stages of diabetes. Shenkang injection (SKI) has shown promising effects on DKD, but its mechanism has not been fully elucidated. Therefore, this study aims to investigate the mechanism by which SKI reduces kidney inflammatory injury and delays DKD progression.MethodsSeveral db/m mice were used as the control group, while db/db mice were randomly divided into the model group, the dagliflozin group, and the SKI group. HK-2 cells were cultured in vitro and divided into the control group, high glucose group, SKI group, and SB203580 group. In this study, the therapeutic effect of SKI on DKD was evaluated by observing the general condition of the mice alongside blood and urine biochemical indices. TEM, HE staining, PAS staining, and Mallory staining were utilized to assess the pathological injury of renal tissue. Immunohistochemistry, WB, and real-time qPCR were employed to detect the expression of the key proteins involved in the mechanisms in mouse renal tissue and HK-2 cells.ResultsThe results indicated that the general condition and kidney injury were significantly improved in the SKI group, as evidenced by reduced urinary protein quantification, urinary albumin-to-creatinine ratio, SCr, and urea levels (P<0.01). Routine staining and TEM analyses demonstrated significant improvement in podocyte injury and renal interstitial fibrosis. The CCK-8 results demonstrated high cell survival rates in the SKI group. There were significant decreases in p-p38, p-NFκB, MCP-1, and CCR2 levels (P<0.05, P<0.01), with no statistical differences observed for p38 and NFκB. Real-time qPCR revealed significant reductions in MCP-1 and CCR2 mRNA expression in the SKI group (P<0.01).ConclusionSKI can reduce kidney inflammatory damage in db/db mice, improve kidney function, and delay the progression of diabetes. The mechanism may involve the reduction of MCP-1/CCR2 activation through the p38 MAPK/NFκB signaling pathway.